Ecological problem identification based on spatial and temporal dynamics of ecosystem quality: A case study - Rui Zhang; Huamin Liu; Zhichao Xu; Xinchuan Zhao; Lu Wen; Yi Zhuo; Lixin Wang (Ecological Indicators)
Bayannur, located in the Hetao Plain and the Urat Grassland, is China’s important ecological security barrier. It plays a significant role in the country’s sustainable socio-economic development, ecological protection, and high-quality growth. However, in recent years, the region’s ecosystem has faced increasing pressure due to rapid population growth, urbanization, industrialization, intensified human-land conflicts, and global climate change. We utilize multi-source remote sensing data and GIS technology to analyze land use patterns and the Ecological Quality Index (EQI). By examining the spatial and temporal changes in ecosystem quality across different ecosystems in Bayannur, we aim to identify areas experiencing significant ecological degradation. Through a driver analysis, the aim is to identify the main influences on changes in ecosystem quality in different ecosystems. The study found that: (1) Resource utilization efficiency varies among ecosystems in Bayannur, with human activities significantly impacting local ecosystems; (2) Ecological quality shows substantial variation over time and across regions. While ecological conditions have improved in some areas over recent decades, severe degradation persists in the northwest. The impact of anthropogenic activities and arid climatic conditions are the main causes of these changes in ecological quality; (3) The distribution of ecosystems reveals distinct regional differences. The southern agricultural area demonstrates healthier ecosystem conditions, whereas the northwestern desert and northern grassland areas face serious degradation challenges, particularly desertification and grassland decline. Compared to traditional methods, our approach provides a more integrated and spatio-temporally detailed analysis by combining remote sensing data with the EQI. Based on these degradation patterns, this study proposes targeted governance strategies. The findings of this study hold both theoretical and practical significance for ecological protection and sustainable development in the region.